Synthesis and characterization of sulfonated block copolyimides derived from 4, 4'‐sulfide‐bis(naphthalic anhydride) for proton exchange membranes. Issue 8 (1st October 2014) - Chen, Guofei; Pei, Xueliang; Wei, Haibing; Xu, Lubo; Fang, Xingzhong
ABSTRACT A series of sulfonated copolyimides (SPIs) with hydrophilic segment length of 20–60 based on 4, 4′‐sulfide‐bis(naphthalic anhydride) (SBNA) have been successfully synthesized to improve hydrolytic stability and proton conductivity. The SPI membranes were cast from their m‐cresol solutions, and they were characterized by determining the water uptake, water swelling ratio, mechanical properties, hydrolytic stability, oxidative stability, and proton conductivity. It was found that the water uptake of SPI membranes was low and decreased as the hydrophilic segment length increased, which led to good dimensional stability. In addition, the SPI membranes with low ion‐exchange capacity (IEC) value displayed excellent hydrolytic stability and retained good mechanical properties even after harsh hydrolysis testing, in which the block SPI with hydrophilic segment length of 40 had the best hydrolytic stability, while those with high IEC value showed an apparent decrease. All of the block SPI membranes show better conductivity than the random ones at the temperature range from 30 to 70°C. Interestingly, the proton conductivities of random SPI membranes were higher than that of corresponding block ones at 90°C. The block SPI with hydrophilic segment length of 40 gave the highest proton conductivity as the temperature increased among the block SPIs. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41501.